Negotiating the Deal. - Johnson, Kerry (Kerry L.) (G&D Media, 2022)
Negotiation doesn't have to be a win-loss game...you can strike a deal good for everyone but the skill lies in negotiating in a way that relationships can be built, developed and maintained.